Understanding socio-economic and policy constraints to dairy development in Ethiopia: A coupled functional-structural innovation systems analysis - Ergano, Kebebe; Duncan, Alan J.; Klerkx, Laurens; Boer, Imke J.M. de; Oosting, Simon J. (Elsevier, 2015)
This study investigates how the Ethiopian dairy innovation system has functioned to support the development of the Ethiopian dairy sector and what have been the major technical, economic, and institutional constraints in the process. We used a coupled functional–structural analysis of innovation systems to analyse the influence of socio-economic and policy constraints on the development of the Ethiopian dairy sector. Results show that problems with structural elements such as the absence of key actors, limited capacity of existing actors, insecure property rights, cumbersome bureaucratic processes, poor interaction among actors and inadequate infrastructure have all limited dairy innovation. Out of the seven innovation system functions studied, our findings show that entrepreneurship, knowledge diffusion, market development and legitimacy creation have been particularly weak. Our evidence thus suggests that problems with certain structural elements coupled with weaknesses in various innovation system functions have been major hindrances to the uptake of technologies and dairy sector development in Ethiopia. The narrow policy focus on biophysical technology generation and dissemination, without considering the underlying problems related to institutional conditions and socio-economic processes, has also contributed to low technology adoption and limited broader development in the dairy sector. We suggest that combinations of institutional and technological interventions are needed to overcome the various system weaknesses that have hindered dairy sector development in Ethiopia.